One-pot synthesis of CuPt nanodendrites with enhanced activity towards methanol oxidation reaction. Issue 17 (5th March 2018) - Peng, Hongcheng; Qi, Weihong; Wu, Haofei; He, Jieting; Li, Yejun; Xie, Haipeng
Abstract : CuPt nanodendrites have special electrocatalytic performance due to their unique morphology and structures. Abstract : CuPt nanodendrites have special electrocatalytic performance due to their unique morphologies and structures. In this work, we report a facile and one-pot synthesis of highly branched and dispersed CuPt nanodendrites with a size of about 22 nm and Pt/Cu ratio of 2 : 1. X-ray photoelectron spectra indicate a Pt-rich surface of the prepared CuPt nanodendrites. The combination of a highly branched structure with a Pt-rich shell would be very beneficial for catalytic properties, which was confirmed by electrochemical tests towards MOR. A systematic study on morphology evolution of the products and understanding of their growth mechanism was carried out using the effects of reaction time and reducing agents.